Digital Advertising and Purchasing: Fun or a New Type of Deception? - Kenneth Julli (International Telecommunications Society (ITS), 2019)
The digital world operates differently from the old world of print media. Notably, online advertising and purchasing are performed in a fast paced and interactive process. When purchasing online, the first screen a consumer sees is similar to the print advertisements of old. However, unlike print advertising, the first digital screen gives way to an interactive process as the consumer clicks through pages to complete their online transaction. The Organisation for Economic Co-operation and Development (OECD) has observed that "trust is essential in situations where uncertainty and interdependence exist." Existing laws that govern misleading and deceptive advertising must be adapted to the new digital world. Consumers need to have trust that the prices they see online are the prices they will actually pay as they click through to complete their transaction. In recognition of the importance of digital platforms, and the high levels of trust consumers place in the digital world, governments are beginning to develop regulations specific to the digital world. Additionally, and more than ever, regulators such as the Canadian Competition Bureau are responding to evolving challenges in the digital economy. In particular, the Bureau's Deceptive Marketing Practices Directorate has committed to investigating misleading representations made online to foster a transparent digital economy in line with consumer protection...
Keywords: 330